A model for developing the legal competence of vocational education teachers in vocational education institutions of the construction industry - Natesa, Denys (ScienceRise: Pedagogical Education, 2026)
The article is devoted to the presentation of the scientific activity results on the development and substantiation of the development model of the legal competence of teachers in vocational education institutions of the construction industry. The current state of scientific development of the problem of modeling the development of teacher competence, in particular, the legal competence of teachers in vocational education institutions of the construction industry, is analyzed. Foreign models of organizing teacher training are considered, which, in particular, provide for the participation of socially responsible business in educational projects; taking into account the features of "greening technical and vocational education and training" in the model of pedagogical competence of a teacher of vocational education in the context of sustainable development; integration of the needs of the industry, attitudes and ICT and new knowledge, existing skills, abilities, practices, assessment and reflection; individually managed learning, study groups and trainings that meet the needs of teachers will improve their leadership and the effectiveness of educational activities. Thesaurus of the problem of forming the value formation of a personality in an artistic and aesthetic educational environment is substantiated. The term development model of the legal competence of vocational training teachers in vocational education institutions of the construction industry is interpreted as a structurally integrated system that reflects the patterns, principles, content, stages and mechanisms of formation of professionally significant legal knowledge, skills and value orientations of teachers. It is aimed at ensuring the readiness of teachers for the effective use of legal norms in pedagogical activity, which includes methodological support of the educational process, creation of legal culture among students. The author’s vision of the development model of the legal competence of vocational training teachers in vocational education institutions of the construction industry is proposed. Its main components are defined as target-motivational, content-procedural and effective blocks, which are determined by the pedagogical conditions we have identified